Offside: The Misunderstanding in Restricting Jemaat Ahmadiyah Indonesia's Right to Freedom of Religion - Ahmad, Ansar; Ramadhani, Tasya Nur (Universitas Pelita Harapan, 2022)
Jemaat Ahmadiyah Indonesia (